Development of Early Childhood Science Literacy E-Modules Base Learning Project Method - Khairiah, Fisna; Eliza, Delfi; Rakimahwati, Rakimahwati; Mayar, Farida (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Learning science Not yet held optimally in Kindergarten Because Not yet availability of facilitating learning media child For carry out activity learning. This is also based on that based on results Pisa 2022 with the score dropped from year Previously, it was caused by facilities learning and learning media used. The main purpose study This is For developing method project literacy science. Literacy science based _ The base learning project is a centered learning model to child, so educator as facilitator. Types of research This use preliminary research which is part from study This is the model used is adopted development from Borg & Gall. Instruments used questionnaires and guidelines observation. Subjects involved _ are teacher and child age early childhood aged 5-6 years, totaling 14 children. Analysis done with method percentage, results analysis explained based on formulas and processing in data collection, planning, development draft product, and testing as well as revision from test results that have been carried out done. The implications can used in activity diverse and interesting learning _ with literacy science.